2019
DOI: 10.15376/biores.14.2.3630-3650
|View full text |Cite
|
Sign up to set email alerts
|

Salt-template hydrothermal carbonization for Pd NP-loaded porous carbonaceous material

Abstract: Inorganic salt is a promising stabilizer in the hydrothermal synthesis of porous carbon materials. A three-dimensional palladium-loaded (Pd-loaded) lignin carbonaceous material with a porous structure was developed via hydrothermal carbonization, with lignin as not only a carbon source but also a reducing and stabilizing agent for palladium nanoparticles (Pd NPs) and then with LiCl as the hard template and porogen. The porogen-induced Pd-loaded carbonaceous material displayed an orderly pore structure with mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…29 From this data, along with the TEM images, which demonstrate wrapping of the LIG around embedded salt particles, we believe that the salt particles act as a template or porogen in the PFA composite, enabling the formation of a higher surface area carbon material. Salt particles such as LiCl have been utilized in this manner as a hard template during the hydrothermal carbonization of lignin, to result in a higher surface area carbon material, 43 and salts such as ZnCl 2 and Na 2 CO 3 have been employed in the chemical activation of carbons at high temperature to boost carbon surface areas. 41 XPS analysis was then performed on the LIG powders to further investigate their chemical structures.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…29 From this data, along with the TEM images, which demonstrate wrapping of the LIG around embedded salt particles, we believe that the salt particles act as a template or porogen in the PFA composite, enabling the formation of a higher surface area carbon material. Salt particles such as LiCl have been utilized in this manner as a hard template during the hydrothermal carbonization of lignin, to result in a higher surface area carbon material, 43 and salts such as ZnCl 2 and Na 2 CO 3 have been employed in the chemical activation of carbons at high temperature to boost carbon surface areas. 41 XPS analysis was then performed on the LIG powders to further investigate their chemical structures.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Likewise, salt particles have been previously utilized as templating and pore-forming agents in order to increase the porosity and surface area of carbon materials. 43 Herein, we demonstrate that the addition of micron-sized particles of sodium salts such as sodium chloride (NaCl) and sodium sulfate (Na 2 SO 4 ) into PFA dramatically changes the resulting LIG material after laser irradiation. The addition of salt particles increases the BET surface area of the LIG formed by over an order of magnitude and also results in the formation of either Cl-or S-doped LIG depending on the salt used, resulting in LIG electrodes that exhibit a capacitance ∼2500× that of pristine PFA.…”
Section: ■ Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The slender wood cells were mainly composed oriented cellulose elementary fibrils and the matrix of hemicellulose and lignin. And the meddle lamella are mainly composed of lignin [19] . Our preliminary research has shown that the delignified wood composed of well‐aligned microchannels (mainly composed of aligned cellulose microfibrils) and abundant intertubular cavities (space of the middle lamella lignin) possess good mechanical flexibility [20] .…”
Section: Introductionmentioning
confidence: 99%
“…And the meddle lamella are mainly composed of lignin. [19] Our preliminary research has shown that the delignified wood composed of well-aligned microchannels (mainly composed of aligned cellulose microfibrils) and abundant intertubular cavities (space of the middle lamella lignin) possess good mechanical flexibility. [20] After carbonization, the delignified wood-based carbon materials also exhibit good mechanical flexibility.…”
Section: Introductionmentioning
confidence: 99%